Masyarakat Nelayan dalam Merawat Multikulturalisme - Liata, Nofal; Alawiyah, Tuti; Natasya, Zahwa (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2024)
This study explores the concept of multiculturalism within the fisherman community of Pusong Village, Lhokseumawe, Aceh Province. Here, multiculturalism naturally emerges among low-income and fisherman populations, not upheld by the educated members of the society. This research aims to identify how multiculturalism is maintained in a village that has historically grown on the outskirts of Lhokseumawe since the beginning of Indonesia's independence. The focus is on understanding the existing social relationship patterns, exploring the multicultural understanding developed by the community, and investigating why the majority of the fisherman community accepts a diversity of ethnicities and religions in their village. A qualitative descriptive methodology was employed, with data gathered through field observations, in-depth interviews, and relevant literature analysis. The findings reveal that the sustenance of multiculturalism in Pusong Village is supported by communal empathy, active roles of community leaders as models of socialization, high social concern, social interactions transcending individual backgrounds, and strong adherence to local norms and rules. Multiculturalism in Pusong Village organically evolves, significantly influenced by the economic and social dynamics associated with the village's position as a port and market area. This study demonstrates how ethnic and religious diversity in Pusong Village can serve as an exemplar of how diversity can promote social harmony and enhance communal welfare.Abstrak: Penelitian ini menggali konsep multikulturalisme dalam komunitas nelayan di Desa Pusong, Lhokseumawe, Provinsi Aceh. Dalam studi ini, multikulturalisme muncul secara alami di kalangan masyarakat berpendapatan rendah dan buruh nelayan, bukan dikawal oleh warga berpendidikan. Fokus penelitian ini adalah untuk mengidentifikasi bagaimana multikulturalisme dipertahankan di desa yang secara historis tumbuh di pinggiran kota Lhokseumawe sejak awal kemerdekaan Indonesia. Penelitian ini bertujuan untuk memahami pola hubungan sosial yang ada, menggali pemahaman multikultural yang dibangun oleh masyarakat, dan menjelajahi alasan penerimaan ragam etnis dan agama oleh mayoritas masyarakat nelayan di desa tersebut. Metodologi yang digunakan adalah deskriptif kualitatif, dengan data dikumpulkan melalui observasi lapangan, wawancara mendalam, dan analisis literatur yang relevan. Hasil penelitian menunjukkan bahwa pemeliharaan multikulturalisme di Desa Pusong didukung oleh empati antar komunal, peran aktif tokoh masyarakat sebagai model sosialisasi, kepedulian sosial yang tinggi, interaksi sosial yang melampaui latar belakang individu, dan pengikatan kuat pada norma serta aturan lokal. Multikulturalisme di Desa Pusong berkembang secara organik, terutama dipengaruhi oleh dinamika ekonomi dan sosial yang berhubungan dengan posisi desa sebagai area pelabuhan dan pasar. Penelitian ini mengungkapkan bahwa adaptasi dan toleransi yang terjadi di Desa Pusong dapat menjadi contoh bagaimana diversitas etnis dan agama dapat mempromosikan harmoni sosial dan meningkatkan kesejahteraan komunal.